1996
DOI: 10.1038/380072a0
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced dihydropyridine receptor channel activity in the presence of ryanodine receptor

Abstract: Excitation-contraction coupling in skeletal muscle involves a voltage sensor in the plasma membrane which, in response to depolarization, causes an intracellular calcium-release channel to open. The skeletal isoform of the ryanodine receptor (RyR-1) functions as the Ca2+-release channel and the dihydropyridine receptor (DHPR) functions as the voltage sensor and also as an L-type Ca2+ channel. Here we examine the possibility that there is a retrograde signal from RyR-1 to the DHPR, using myotubes from mice homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
457
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 445 publications
(489 citation statements)
references
References 29 publications
31
457
1
Order By: Relevance
“…Such a signal is termed retrograde signalling [10]. Chavis et al have shown a similar signal in cerebellar granule cells [12], where RyRs activated by type-1 metabotropic glutamate receptors increase VACC activity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Such a signal is termed retrograde signalling [10]. Chavis et al have shown a similar signal in cerebellar granule cells [12], where RyRs activated by type-1 metabotropic glutamate receptors increase VACC activity.…”
Section: Discussionmentioning
confidence: 97%
“…The cardiac and brain isoforms of type-2 RyRs (RyR-2) and brain isoforms of type-3 RyRs (RyR-3) [5,6] are activated by cADPR [7,8], but the skeletal-muscle isoforms of type-1 RyRs (RyR-1) are not [8,9]. Whereas RyR-1 is coupled to L-type voltage-activated Ca# + channels (VACCs) through proteinprotein interactions [10], such direct coupling has not been shown in RyR-2 and RyR-3. In neurons, instead, a link from Ntype VACCs to RyRs (an orthograde influence) [11] and a functional coupling from RyRs to L-type VACCs (a retrograde signal) [12] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Our results support the hypothesis of a retrograde communication between the SR Ca 2+ release channel and the L-type Ca 2+ channel (DHPR). This communication may be mediated in some cases by a direct interaction between the two channel proteins, L-type Ca 2+ channel and RyR 2 [33]. Effects of siRNA3 target on mRNA and protein levels of RyR 2 in rat primary cardiomyocytes with transfection after 6-72 h tested by RT-PCR and western blot.…”
Section: Discussionmentioning
confidence: 99%
“…They found faster activation and inactivation kinetics of DHPRs incorporated in lipid bilayers when purified RyR1 was added to the cis-chamber. However, the term "retrograde signaling" was coined several years later when DHPR-RyR interactions were investigated by electrophysiological characterization of dyspedic skeletal muscle myotubes (Nakai et al 1996). Dyspedic myotubes have a homozygous mutation of the RyR1 gene and do not express functional RyR Ca 2+ release channels.…”
Section: Retrograde Ryr-dhpr Couplingmentioning
confidence: 99%